OHP-010 VAC therapy to reduce surgical wound complications: the opinion of the pharmacist. (24th March 2015) - Capozzi, M; Di Maso, L; Sarno, M; Maiolino, P
Abstract : Background: Vacuum Assisted Closure (VAC) treatment is an innovative system that promotes wound healing by applying negative pressure (vacuum) at the wound site. The use of VAC Therapy removes oedema fluid, increases blood flow and cell proliferation and reduces bacterial colonisation. Purpose: Since oncological surgery is often radical with a long rehabilitation phase and complications with the surgical wound, the physicians decided to use VAC Therapy to help two patients to recover from serious operations. After a careful study of related literature, pharmacists addressed the supply, ensuring the prescribed device was safe and clinically appropriate. Material and methods: In this pilot experiment VAC Therapy was used on two patients: D. G. M., female, aged 76, suffering from abdominal wall sarcoma. M. L., male, aged 78, suffering from sacral chordoma. Pharmacy databases and electronic medical records were also evaluated. Results: Both patients had undergone complete resection of the tumour. After surgery VAC Therapy was used. Patient D. G. M. was treated for 6 weeks and regained full functionality in 120 days, for a total cost of €2, 219.00. Patient M. L. was treated for 2 weeks and regained full functionality in 60 days, for a total cost of €669.90. No complications were recorded and the treatment was well tolerated with a therapeutic compliance of 100%. Conclusion: VAC Therapy avoids further extensive reconstructive operations allowing fast patient recovery. The device is expensive but it can be a valid option for patients with high risk of poor healing and reduced compliance. The cost can be written off by reducing the time of hospitalizations, and risk of complications and infections. The pharmacist played a key role in the choice of the most appropriate treatment for the patient and cost/benefit valuation. Reference: Kaplan M. Negative pressure wound therapy in the management of abdominal compartment syndrome. Ostomy Wound Manage 2009;51 (2A Suppl):29–35S No conflict of interest.